Meningkatkan Kemampuan Sains Melalui Eksperimen Telur Pada Anak di TK Amzar Molinow Kota Kotamobagu - Paputungan, Hasnawati (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to improve science skills through egg experiments on children at Amzar Molinow Kindergarten, Kotamobagu City. Based on the results of research carried out, where the development of children's science through egg experiments has never been done by teachers. The experiment is still not carried out, this is because children are more dominant in playing than learning. This can affect the success of the teaching and learning process in the classroom, so automatically student learning outcomes do not achieve optimal results. This research was conducted through two cycles with a classroom action research model that refers to the Kemmis and Mc. Taggart which consists of four stages, namely: 1. Planning, 2. Implementation, 3. Observation, 4. Reflection. The research subjects were 9 students at Amzar Molinow Kindergarten. Data collection techniques used are observation, tests, and documentation. The results showed that the use of egg experiments to improve science skills in children showed a good change with the results obtained in the first cycle reaching 66.6%, while in the second cycle the results obtained by students had increased to 100%%. So it can be said that the increase in cycle I to cycle II is 33.4%. Based on the results of research and discussion, it can be concluded that the egg experiment can improve science skills and can improve student learning outcomes.